Low-oil-stain adhesiveness preservation box cover and preparation method thereof

By mixing polypropylene and trifluoropropyltrimethoxysilane and subjecting it to plasma treatment, a crisper lid with low oil stain adhesion is prepared, which solves the problems of oil stain adhesion and penetration of existing food packaging materials and achieves low oil stain adhesion. Cost-effective, safe oleophobic effect and nano-level microstructure.

CN119320528AInactive Publication Date: 2025-01-17YANGZHOU YUJING DAILY PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411439209.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing food packaging materials have problems in the adhesion and penetration of oil stains, which affects food quality and safety. Traditional oleophobic technology has problems such as high production costs, difficult processing, and safety threats.

Method used

By mixing polypropylene with trifluoropropyltrimethoxysilane and undergoing plasma treatment, a crisper lid with low oil adhesion is prepared. This method achieves a low-cost, high-safety oleophobic effect through the screening of raw materials and the optimization of the production process.

Benefits of technology

It achieves a significant reduction in the surface energy of the material, enhances the oleophobicity, forms a nano-level microstructure, has significant self-cleaning ability, is suitable for mass production, and complies with food safety standards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of preservation boxes, particularly provides a low-oil-stain-adhesiveness preservation box cover and a preparation method thereof, and aims to improve the oleophobicity and wear resistance of the preservation box cover. The method comprises the following steps: carrying out melt blending on polypropylene and trifluoropropyltrimethoxysilane in a twin-screw extruder to prepare a mixture, molding a fresh-keeping box cover blank through an injection molding process, and then carrying out low-temperature plasma treatment on the blank to obtain the fresh-keeping box cover with low oil stain adhesiveness. Preferably, the trifluoropropyl trimethoxy silane can be modified with the nano silicon dioxide, and oleophobic surface nano particles are generated through reaction with hydroxyl on the surface of the nano silicon dioxide. Implementation results show that the preservation box cover subjected to modification treatment shows excellent properties in both oleophobicity and wear resistance, especially can still keep a relatively high oleophobic angle after friction, and shows relatively good durability and oil stain prevention effect. The method is simple and feasible, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fresh-keeping boxes, and in particular to a fresh-keeping box cover with low oil stain adhesion and a preparation method thereof. Background Art

[0002] With the improvement of food safety and environmental awareness, the development and application of food packaging materials have received increasing attention. Traditional food packaging materials often face the problem of oil adhesion and penetration, which not only affects the quality and safety of food, but also brings troubles to consumers' experience. Therefore, the development of food packaging materials with good oleophobic properties is an important topic in the industry.

[0003] At present, conventional oleophobic technical means mainly include: 1. Processing a coating structure with oleophobic function on the surface of the packaging material, and using the oleophobic coating structure to achieve the oleophobic effect; 2. Adding materials with oleophobic function to the preparation of raw materials, so that the packaging material itself has a certain oleophobicity; 3. Processing a specific oleophobic structure on the surface of the packaging material to improve the oleophobic performance of the packaging material. The above-mentioned scheme of adding an oleophobic coating structure will not only increase the production cost and increase the difficulty of processing, but also the stability of the coating structure will pose a certain safety threat to food. It is technically difficult to screen out safe and reliable coating materials, and the development cost is high. Although the method of directly adding oleophobic functional materials is simple and the cost is low, the oleophobic material itself needs to comply with food safety regulations. At the same time, the oleophobic effect achieved by the addition of oleophobic materials is limited. Processing a specific oleophobic structure can effectively circumvent safety issues, but this type of oleophobic microstructure has extremely high requirements for production and processing molds, which is not conducive to reducing production costs.

[0004] In view of this, providing a safe and reliable fresh-keeping box cover with low oil adhesion that is easy to process and produce has become one of the technical problems that need to be solved urgently. Summary of the invention

[0005] In view of this, the present invention proposes a fresh-keeping box cover with low oil adhesion and a preparation method thereof, aiming to achieve a low-cost and high-safety technical solution for the fresh-keeping box cover with low oil adhesion through the screening of raw materials and the optimization of the production process.

[0006] The technical solution of the present invention is implemented as follows: The present invention provides a method for preparing a fresh-keeping box cover with low oil adhesion, the method comprising the following steps:

[0007] Step 1, mixing polypropylene and trifluoropropyltrimethoxysilane to obtain a mixed material;

[0008] Step 2: Extruding the mixed material through an extruder to form a fresh-keeping box cover blank by injection molding;

[0009] Step 3: subjecting the formed fresh-keeping box cover blank to low-temperature plasma treatment on its surface, using argon as a plasma source, treating for 10-30 seconds, with a treatment power of 100-300W, and cooling and curing after the plasma treatment to obtain a fresh-keeping box cover with low oil adhesion.

[0010] Polypropylene as a substrate provides mechanical strength and food safety, and the fluorine groups in trifluoropropyltrimethoxysilane form a low surface energy structure on the surface of the material, effectively enhancing oleophobicity. Plasma treatment further enhances the differentiation of surface energy, eliminating lipophilic sites and leaving oleophobic chemical functional groups.

[0011] In some embodiments, the raw materials, calculated by weight, include: 70-90 parts of polypropylene and 1-3 parts of trifluoropropyltrimethoxysilane.

[0012] The precise raw material ratio ensures that the mechanical properties of polypropylene are maintained in the substrate while utilizing the oleophobic properties of trifluoropropyltrimethoxysilane. The trifluoropropyl groups gather on the surface of the material to form an effective oleophobic barrier, and the ratio setting ensures the uniform distribution of the silane.

[0013] In some embodiments, the trifluoropropyltrimethoxysilane is modified by mixing nano-silica and fluorosilane in a ratio of (0.1-2):1, heating to 70°C-100°C, stirring evenly, and reacting for 2-4 hours. Fluorosilane reacts with hydroxyl groups on the surface of nano-silica to generate oleophobic nanoparticles.

[0014] The fluorine group of trifluoropropyltrimethoxysilane reacts with the surface of nano-silica to form oleophobic nanoparticles. These nanoparticles are distributed on the surface of the polypropylene substrate, further increasing the microscopic roughness of the surface and making it more oleophobic. Nanoparticles help to form a self-cleaning ability similar to the lotus effect by increasing the microstructure of the surface.

[0015] In some embodiments, in step 1, the mixing method includes melt blending polypropylene and trifluoropropyltrimethoxysilane in a twin-screw extruder, with a melting temperature of 180-220° C., a rotation speed of 100-200 rpm, and a mixing time of 5-10 min.

[0016] By controlling the melt temperature (180-220°C) and screw speed (100-200rpm), the uniform blending of polypropylene and trifluoropropyltrimethoxysilane is achieved. The efficient mixing conditions ensure that the silane molecules are evenly distributed in the polypropylene matrix, maximizing the oleophobic effect while ensuring the mechanical properties of the material.

[0017] In some embodiments, in step 2, the extrusion die temperature is 180-210°C.

[0018] By precisely controlling the extrusion die temperature, the fluidity and molding accuracy of the material during the molding process are guaranteed. This temperature range can not only maintain the fluidity of polypropylene, but also prevent the oleophobic agent from decomposing at high temperatures.

[0019] In some embodiments, in step three, the cooling and curing step is: naturally cooling the fresh-keeping box cover after plasma treatment in a cooling chamber.

[0020] After plasma treatment, the surface chemical groups are activated, and the surface oleophobic effect and stable microstructure are maintained through natural cooling and solidification. Natural cooling avoids the internal stress of the material caused by rapid cooling, ensuring the durability of the product.

[0021] In a second aspect, the present invention further provides a fresh-keeping box cover with low oil adhesion prepared based on the above preparation method.

[0022] The fresh-keeping box cover has an oleophobic surface structure through reasonable raw material ratio, mixing process, surface treatment and cooling solidification. Plasma treatment forms a uniform oleophobic coating on the surface of the fresh-keeping box cover, while ensuring the durability and cleanliness of the product during use.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention significantly reduces the surface energy of the material by introducing trifluoropropyltrimethoxysilane. After combined with plasma treatment, the surface active groups are removed and the oleophobic groups are retained to form a nano-scale microstructure, thereby achieving an oleophobic effect. The scheme is simple and feasible, and has the advantages of low cost, stable process, and suitability for large-scale production, and meets food safety standards. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0027] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0028] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0029] Example 1

[0030] Raw materials: 85 g polypropylene, 2 g trifluoropropyltrimethoxysilane.

[0031] Preparation process:

[0032] 1. Polypropylene and trifluoropropyltrimethoxysilane were mixed in a twin-screw extruder at a melt temperature of 200°C at 150 rpm for 8 minutes.

[0033] 2. The extrusion temperature was set at 190°C and the kneaded product was injection molded.

[0034] 3. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 20 seconds, and the treatment power is 200W.

[0035] 4. Allow to cool naturally after processing.

[0036] Example 2

[0037] Raw materials: 75 g polypropylene, 3 g trifluoropropyltrimethoxysilane.

[0038] Preparation process:

[0039] 1. Polypropylene and trifluoropropyltrimethoxysilane were mixed in a twin-screw extruder at a melt temperature of 190°C at 180 rpm for 7 minutes.

[0040] 2. The extrusion temperature was set at 200°C and the kneaded product was injection molded.

[0041] 3. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 30 seconds, and the treatment power is 250W.

[0042] 4. Allow to cool naturally after processing.

[0043] Example 3

[0044] Raw materials: 90 g polypropylene, 1.5 g trifluoropropyltrimethoxysilane.

[0045] Preparation process:

[0046] 1. Polypropylene and trifluoropropyltrimethoxysilane were mixed in a twin-screw extruder at a melt temperature of 220°C at 120 rpm for 6 minutes.

[0047] 2. The extrusion temperature was set at 210°C and the kneaded product was injection molded.

[0048] 3. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 15 seconds, and the treatment power is 300W.

[0049] 4. Allow to cool naturally after processing.

[0050] Example 4

[0051] Raw materials: 85g polypropylene, 4g modified trifluoropropyltrimethoxysilane.

[0052] Preparation process:

[0053] 1. Mix nano-silica and trifluoropropyltrimethoxysilane in a ratio of 1:1, heat to 80°C, stir evenly, and react for 2 hours. Trifluoropropyltrimethoxysilane reacts with the hydroxyl groups on the surface of nano-silica to generate oleophobic surface nanoparticles.

[0054] 2. Polypropylene and modified trifluoropropyltrimethoxysilane were kneaded in a twin-screw extruder at 200°C and 150 rpm for 8 minutes.

[0055] 3. The extrusion temperature was set at 190°C and the kneaded product was injection molded.

[0056] 4. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 20 seconds, and the treatment power is 200W.

[0057] 5. Allow to cool naturally after processing.

[0058] Example 5

[0059] Raw materials: 85 g polypropylene, 6 g modified trifluoropropyltrimethoxysilane.

[0060] Preparation process:

[0061] 1. Mix nano-silica and trifluoropropyltrimethoxysilane in a ratio of 2:1, heat to 90°C, stir evenly, and react for 3 hours. Trifluoropropyltrimethoxysilane reacts with the hydroxyl groups on the surface of nano-silica to generate oleophobic surface nanoparticles.

[0062] 2. Polypropylene and modified trifluoropropyltrimethoxysilane were kneaded in a twin-screw extruder at 200°C and 150 rpm for 8 minutes.

[0063] 3. The extrusion temperature was set at 190°C and the kneaded product was injection molded.

[0064] 4. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 20 seconds, and the treatment power is 200W.

[0065] 5. Allow to cool naturally after processing.

[0066] Comparative Example 1

[0067] Raw materials: polypropylene 100g.

[0068] Preparation process:

[0069] 1. Polypropylene was kneaded in a twin-screw extruder at a melt temperature of 200°C at 150 rpm for 8 minutes.

[0070] 2. The extrusion temperature was set at 190°C and the kneaded product was injection molded.

[0071] 3. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 20 seconds, and the treatment power is 200W.

[0072] 4. Allow to cool naturally after processing.

[0073] Comparative Example 2

[0074] Raw materials: 85 g polypropylene, 2 g trifluoropropyltrimethoxysilane.

[0075] Preparation process:

[0076] 1. Polypropylene and trifluoropropyltrimethoxysilane were mixed in a twin-screw extruder at a melt temperature of 200°C at 150 rpm for 8 minutes.

[0077] 2. The extrusion temperature was set at 190°C and the kneaded product was injection molded.

[0078] 3. Allow to cool naturally after processing.

[0079] Comparative Example 3

[0080] Raw materials: 85g polypropylene, 2g trifluoropropyltrimethoxysilane, 2g nano-silicon dioxide.

[0081] Preparation process:

[0082] 1. Polypropylene, modified trifluoropropyltrimethoxysilane and nano-silica were mixed in a twin-screw extruder at 200°C and 150 rpm for 8 minutes.

[0083] 2. The extrusion temperature was set at 190°C and the kneaded product was injection molded.

[0084] 3. The formed fresh-keeping box cover is subjected to plasma treatment, with argon gas as the plasma source, the treatment lasts for 20 seconds, and the treatment power is 200W.

[0085] 4. Allow to cool naturally after processing.

[0086] The fresh-keeping box covers prepared in the above-mentioned embodiments and comparative examples were subjected to performance tests, including oleophobicity test, oil stain adhesion test and wear resistance test.

[0087] Oleophobicity test: The oleophobicity of the surface is evaluated by contact angle test.

[0088] Oil adhesion experiment: Apply grease to the surface of the box cover, let it stand for 2 hours, then clean it and observe the residual oil.

[0089] Wear resistance: After being subjected to the same friction conditions, the oil-repellent effect after friction is tested.

[0090] The results are as follows:

[0091] Grouping Oleophobic angle / ° Oil stain adhesion / mg Surface roughness / nm Abrasion resistance / ° Example 1 105 1.5 150 95 Example 2 110 1.2 140 100 Example 3 100 1.8 160 90 Example 4 120 0.8 120 115 Example 5 125 0.6 110 120 Comparative Example 1 90 3.5 180 70 Comparative Example 2 100 2.0 160 85 Comparative Example 3 100 1.8 135 90

[0092] The oleophobic angle of Example 1 is 105°, which is a relatively conventional oleophobic effect. The amount of oil stains attached is small, and the surface roughness is medium. This shows that the basic trifluoropropyltrimethoxysilane has a significant effect on oleophobicity, but the effect is not optimal.

[0093] In Example 2, by increasing the content of trifluoropropyltrimethoxysilane, the oleophobic angle increased to 110°, the amount of oil adhesion decreased to 1.2 mg, and the surface became smoother, indicating that a higher silane content improved the oleophobic performance.

[0094] In Example 3, due to the low silane content and short plasma treatment time, the oleophobic angle and anti-oil stain ability are both low, and the amount of oil stain adhesion increases. This shows that the oleophobic effect is not ideal when the silane content is low and the treatment time is insufficient.

[0095] After modification by nano-silica, the oleophobic angle of Example 4 was significantly increased to 120°, the amount of oil adhesion was greatly reduced to 0.8 mg, and the surface roughness was reduced, indicating that the modified fluorosilane greatly improved the oleophobic performance.

[0096] In Example 5, the high nano-silica content further increased the oleophobic angle to 125°, the amount of oil adhesion was reduced to 0.6 mg, and the surface roughness was the lowest, indicating that the presence of nanoparticles enhanced the formation of the oleophobic microstructure and the oleophobic performance was the most significant.

[0097] In comparative example 1, pure polypropylene has no oleophobic treatment, the oleophobic angle is only 90°, the amount of oil attached is as high as 3.5 mg, and the surface roughness is the largest, indicating that when no oleophobic treatment is performed, the material surface is easy to absorb oil.

[0098] Comparative Example 2 was not plasma treated, but despite the addition of trifluoropropyltrimethoxysilane, the oleophobic angle was only 100°, and the amount of oil stains attached was large, which shows that plasma treatment is crucial to enhancing oleophobic properties.

[0099] Although trifluoropropyltrimethoxysilane and nano-silicon dioxide were added to Comparative Example 3, the wear resistance was average because no modification was performed, and the oleophobic angle decreased from 100° to 190° after friction. Although its oleophobic performance was better than that of Comparative Example 1 and Comparative Example 2, its wear resistance was average compared with that of Example 4 and Example 5 which were subjected to nano-modification treatment.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fresh-keeping box cover with low oil adhesion, characterized in that: The steps include: Step 1, mixing polypropylene and trifluoropropyltrimethoxysilane to obtain a mixed material; Step 2: Extruding the mixed material through an extruder to form a fresh-keeping box cover blank by injection molding; Step 3: subjecting the formed fresh-keeping box cover blank to low-temperature plasma treatment on its surface, using argon as a plasma source, treating for 10-30 seconds, with a treatment power of 100-300W, and cooling and curing after the plasma treatment to obtain a fresh-keeping box cover with low oil adhesion.

2. The method for preparing the low oil stain adhesion fresh-keeping box cover according to claim 1, characterized in that: The raw materials are calculated by weight and include: 70-90 parts of polypropylene and 1-3 parts of trifluoropropyltrimethoxysilane.

3. The method for preparing the low oil stain adhesion fresh-keeping box cover according to claim 1, characterized in that: The trifluoropropyltrimethoxysilane is modified by mixing nano-silicon dioxide and fluorosilane in a ratio of (0.1-2):1, heating to 70°C-100°C, stirring evenly, and reacting for 2-4 hours. Fluorosilane reacts with hydroxyl groups on the surface of nano-silicon dioxide to generate oleophobic surface nanoparticles.

4. The method for preparing the low oil stain adhesion fresh-keeping box cover according to claim 1, characterized in that: In step 1, the mixing method includes melt blending polypropylene and trifluoropropyltrimethoxysilane in a twin-screw extruder, with a melting temperature of 180-220° C., a rotation speed of 100-200 rpm, and a mixing time of 5-10 min.

5. The method for preparing the low oil stain adhesion fresh-keeping box cover according to claim 1, characterized in that: In step 2, the extrusion die temperature is 180-210°C.

6. The method for preparing the low oil stain adhesion fresh-keeping box cover according to claim 1, characterized in that: In step three, the cooling and curing step is: the fresh-keeping box cover after plasma treatment is naturally cooled in a cooling chamber.

7. A fresh-keeping box cover with low oil adhesion, characterized in that: The low oil adhesion fresh-keeping box cover is prepared by the preparation method described in any one of claims 1-6.

Citation Information

Patent Citations

  • Oil-proof and antibacterial food packaging film

    CN109135209A

  • Hydrophobic and oleophobic self-cleaning material and preparation method thereof

    CN114262480A

  • Easy-to-clean material, preparation method and application thereof

    CN117247586A

  • Hydrophobic and oleophobic high-barrier prefabricated vegetable packaging film and preparation method thereof

    CN118546421A

  • Structure and its Method for Hydrophobic and Oleophobic Modification of Polymeric Materials with Atmospheric Plasmas

    US20110045200A1